Amblyopia of refractive origin: a clinical evaluation - Hossain, Khandaker Anowar; Rashid, Md Abdur; Islam, AKM Rafiqul (Faridpur Medical College Journal, 2015)
Amblyopia is defined as unilateral or bilateral decrease in visual acuity without any organic ocular lesion. It generally develops during the first decade of life when the visual system is vulnerable to deprivation. Unilateral amblyopia is more common than bilateral and the amblyopic eye is called lazy eye. This study was carried out in Faridpur Medical College & Hospital (FMCH) and Diabetic Association Medical College & Hospital (DAMCH) Faridpur, in the department of Ophthalmology from January - 2010 to December 2012 with a view to establish that anisometropic (Refractive) amblyopia is more in patients with astigmatism with the rule of both hypermetropic & myopic types also astigmatism against the rule in hypermetropic patients but simple myopia is not associated with amblyopia. Clinically diagnosed 110 patients of amblyopia of refractive origin were selected. Age of the patients was 6 to 15 years with male & female ratio 1.2:1. There was no pathology in the eyes except refractive error. Refraction done all the cases and found the following results: 26 cases (23.63%) of simple myopic astigmatism with the rule, 19 cases (17.27%) of compound myopic astigmatism with the rule, 10 cases (9.09%) of simple hypermetropia, 38 cases (34.54%) of simple hypermertopic astigmatism with the rule and 17 cases (15.45%) of compound hypermetropic astigmatism againt the rule. No case of simple myopia was associated with amblyopia. Amblyopia was more in patients with astigmatism with the rule of both hypermetropic and myopic types and also astigmatism against the rule in hypermetropic patients but simple myopia was not associated with amblyopia. Faridpur Med. Coll. J. 2014;9(1): 35-36